Effect of silicon on strength and fracture surfaces of aluminium–silicon casting and heat treated alloys - Haque, Md. Mohafizul; Hussein, Nur Izan Syahriah; Ismail, Ahmad Faris (Trans Tech Publications, Switzerland, 2006)
Aluminium-silicon alloys having different silicon contents (13, 20 and 27 percent) were used in the present study. The molten alloys were poured in to a mild steel die to cast tensile test bars. Then tensile and hardness tests were performed in order to analyze the properties and fracture surfaces of the cast specimens. Results show that as silicon content increases, the alloy becomes harder and less ductile. At the same time, the presence of alloying and impurity elements in the alloys forms complex compounds and intermetallic phases. They present deleterious effects on the strength of the alloys, causing a lowering of the energy required to fracture the test specimens with little permanent extension. However, heat treatment operations altered the structures and properties of the aluminium-silicon alloys. Heating to higher temperature, then quenching, ageing and tempering make the alloys stronger up to 13% silicon and beyond that limit the alloys become weaker, fracturing at lower load. The appearance of fracture surfaces after tensile testing showed these differences. This investigation also suggests that for the aluminium-silicon alloys containing 20% and 27% silicon do not require any expensive and time consuming thermal treatment operations, since properties do not improve with such treatments.